Aplikasi Konsep "Ajal" Dalam Al-Quran Menurut Tafsir Al-Azhar Dan Tafsir Al-Misbah Terhadap Keruntuhan Bangsa-Bangsa Muslim - Rahman, Setyadi, Dr. M. Mu'inudinillah Basri, M. A, Prof. Dr. M. Abdul Karim, M.A., M.A (2016)
This research was done because of two problems. First, it is related to searching the meaning of "ajal" that Quran mentions in multiple diverse form and context. It was evident that there is the term of "ajal" is related to decline of umat/community/nation's existence. Second, the decline of Moslem's dynasties that ever built Islamic Empires was the expression of sunnatullah. The writer assumes that (1) their decline did not happen in nature, but it was caused by other factors which repeatedly occured in different places and times; and (2) the factors which are related to the tight to either "ajal" or is "ajal" itself. The two problems appear because of indepth thoughtfulness about the international Moslems condition now, especially the very latest incidents and affairs in Middle East, in the world politic and civilization constellation. This research has three goals they are: (1) explaining the meaning of "ajal" according to Tafsīr al-Azhār by HAMKA and Tafsīr al-Miṣbāh by M. Quraish Shihab; (2) comparing the meaning of "ajal" according to both of them; and (3) applicating the character of "ajal" toward the decline of Moslem nations, espescially the Three Islamic Great Empires in Middle age, they are Ottoman Turkey, Persia's Safawi, and India's Mughal. This research is qualitative library research. The method of data aggregation is tafsir muqārin's method and historical method, and the method of analyzing data is descriptive-analyitic by means of method of language analysis and concept analysis. There are three products of research, they are: (1) the two of mufassir is equal in the term of the meaning of "ajal" that is related to decline of umat by "qadar" or "taqdir", "law of cause-result", and "sunnatullah"; (2) the meaning of "ajal" according to HAMKA is "promise, determinate, or limit", while M. Quraish Shihab is more complete, that is "end limit of things, ages, or activities and affairs" or "limit of destruction and death's time". He also diferentiates between an "individual ajal" and an "ajal of group or community"; and (3) the factors caused the decline of Moslem nations, really materialized in reality after through mechanism of fulfilling qadar or standard/norm/criterion of each factor when interacting between one and others up to certain limits that is culminated in arrival of an "ajal of group or community" as "limit of death's time", and then ending their existence.